The radiological evaluation of anatomical variations of frontal recess in normal population and cases with frontal rhinosinusitis - Küçükgünay, Belgin; Eskiizmir, Görkem; Halis Ünlü, H.; Aslan, Asım; Bayındır, Petek; Yılmaz Ovalı, Gülgün; Özyurt, Beyhan (ENT Updates, 2012)
Objective: In this study, we aimed to evaluate the anatomical variations around frontal recess and the influence of variations on frontal rhinosinusitis (FR) in healthy individuals and in cases with frontal rhinosinusitis (FR). Methods: A total of 61 cases that applied to our outpatient center were grouped according to: cases with ear complaints (Group I, control group), cases with sinonasal symptoms but FR findings (Group II), and cases with both sinonasal and FR findings (Group III). All cases underwent paranasal computerized tomography (CT) with parasagittal reconstruction. All scans were assessed for the presence of fronto-ethmoidal cells, anatomical variations, osteomeatal complex diseases and sinus opacifications. Results: In all sides of study, the rate of fronto-ethmoidal cell was 20.9%. When cases with sinonasal signs (Groups II and III) and control group (Group I) were compared, intersinus septum (p=0.01) and agger nasi cells (p=0.001) were statistically significant. In sides with frontal recess disease (+) and/or frontal sinus opacification (+), Kuhn type III (p=0.03) fronto-ethmoidal cells and bulla frontalis (p=0.02) were significantly increased, and Kuhn type IV fronto-ethmoidal cell (both sides) was present only in cases with frontal recess disease (+) and/or frontal sinus opacification (+). When the role of fronto-ethmoidal cells on frontal recess disease and/or frontal sinus opacification were assessed, Kuhn Type III cell was 4.55 times (%95 GS: 0.560-12.196) more effective. Conclusion: Kuhn type III and IV fronto-ethmoidal cells and bulla frontalis may have a role in FR. The radiological evaluation of anatomical variations around frontal recess with parasagittal sections was useful.